Effects of Long-Term Meditation Practices on Sensorimotor Rhythm-Based Brain-Computer Interface Learning - Jiang, Xiyuan; Lopez, Emily; Stieger, James R.; Greco, Carol M.; He, Bin (Frontiers in Neuroscience, 2021)
Sensorimotor rhythm (SMR) based brain-computer interfaces (BCIs) provide an alternative pathway for users to perform motor control using motor imagery (MI). Despite the non-invasiveness, ease of use and low cost, this kind of BCI has limitations due to long training times and BCI inefficiency— that is, the SMR BCI control paradigm may not work well on a subpopulation of users. Meditation is a mental training method to improve mindfulness and awareness and is reported to have positive effects on one’s mental state. Here we investigated the behavioral and electrophysiological differences between experienced meditators and meditation naïve subjects in 1-dimensional (1D) and 2-dimensional (2D) cursor control tasks. We found numerical evidence that meditators outperformed control subjects in both tasks (1D and 2D), and there were fewer BCI inefficient subjects in the meditator group. Finally, we also explored the neurophysiological difference between the two groups and showed that the meditators had a higher resting SMR predictor, more stable resting mu rhythm, and motor imagery/rest control signal contrast than controls.